Synthesis of Schiff Bases Containing Phenol Rings and Investigation of Their Antioxidant Capacity, Anticholinesterase, Butyrylcholinesterase, and Carbonic Anhydrase Inhibition Properties - Sertan Aytac; Ozlem Gundogdu; Zeynebe Bingol; İlhami Gulcin (Pharmaceutics, 2023)
The widespread usage of Schiff bases in chemistry, industry, medicine, and pharmacy has increased interest in these compounds. Schiff bases and derivative compounds have important bioactive properties. Heterocyclic compounds containing phenol derivative groups in their structure have the potential to capture free radicals that can cause diseases. In this study, we designed and synthesized eight Schiff bases (10–15) and hydrazineylidene derivatives (16–17), which contain phenol moieties and have the potential to be used as synthetic antioxidants, for the first time using microwave energy. Additionally, the antioxidant effects of Schiff bases (10–15) and hydrazineylidene derivatives (16–17) were studied using by the bioanalytical methods of 2,2’-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) cation radical (ABTS•+) and 1,1-diphenyl-2-picrylhydrazyl (DPPH•) scavenging activities, and Fe3+, Cu2+, and Fe3+-TPTZ complex reducing capacities. In the context of studies on antioxidants, Schiff bases (10–15) and hydrazineylidene derivatives (16–17) were found to be as powerful DPPH (IC50: 12.15–99.01 μg/mL) and ABTS•+ (IC50: 4.30–34.65 μg/mL). Additionally, the inhibition abilities of Schiff bases (10–15) and hydrazineylidene derivatives (16–17) were determined towards some metabolic enzymes including acetylcholinesterase (AChE), butyrylcholinesterase (BChE), and human carbonic anhydrase I and II (hCAs I and II), enzymes that are linked to some global disorders including Alzheimer’s disease (AD), epilepsy, and glaucoma. In the context of studies on enzyme inhibition, it was observed that the synthesized Schiff bases (10–15) and hydrazineylidene derivatives (16–17) inhibited AChE, BChE, hCAs I, and hCA II enzymes with IC50 values in ranges of 16.11–57.75 nM, 19.80–53.31 nM, 26.08 ± 8.53 nM, and 85.79 ± 24.80 nM, respectively. In addition, in light of the results obtained, we hope that this study will be useful and guiding for the evaluation of biological activities in the fields of the food, medical, and pharmaceutical industries in the future.